Comparative Evaluation of IFTAK and LAFT Techniques in the Management of Trans-Sphincteric Fistula-in-Ano: A Prospective Study - Pandey, Awadhesh Kumar; Padole, Amol; Pandey, Smita; Habeeb, Nasrin; Thilakan, Aadithyaraj Kunnummal; Dwivedi, Arun Kumar (Journal of Coloproctology, 2025)
Anorectal fistulas are chronic abnormal connections between the anal canal and perianal skin, often resulting from cryptoglandular infections. Despite advancements in surgical techniques, recurrence remains a significant challenge. Traditional methods like fistulotomy and seton placement show variable success rates, while newer sphincter-sparing approaches like IFTAK and LAFT offer promise. This study compares the efficacy of IFTAK and LAFT in managing trans-sphincteric fistulas.This prospective study at Sir Sundar Lal Hospital, BHU, compared IFTAK and LAFT for managing trans-sphincteric fistula-in-ano. Forty-four patients were randomized into two groups (22 each). Patients underwent preoperative preparation, postoperative care, and follow-ups at regular intervals. Outcomes, including pain (VAS), healing, and recurrence, were analyzed statistically using SPSS.Group A (IFTAK) showed significantly lower recurrence rates (0% vs. 27.3%, p = 0.000) and superior healing of the fistulous tract compared to Group B (LAFT). Pain reduction, discharge, inflammation, and induration improved significantly in both groups (p < 0.001). However, Group A demonstrated faster pain reduction and better wound dryness at 45 and 60 days (p < 0.05). Hospital stays were shorter in Group A. Overall, IFTAK exhibited better clinical outcomes and fewer complications.The study indicates that IFTAK is more effective than LAFT for managing trans-sphincteric fistulas, with no recurrences, better healing, and higher success rates, especially for posterior fistulas. LAFT offers less pain, and shorter hospital stays but has a higher recurrence rate. Combining IFTAK and LAFT may optimize outcomes, warranting further research.
Keywords: trans-sphincteric fistula management; IFTAK; LAFT; sphincter preservation; recurrence rate